The Potential of CAR T Cell Therapy in Pancreatic Cancer - Akce, Mehmet; Zaidi, Mohammad Y.; Waller, Edmund K.; El-Rayes, Bassel F.; Lesinski, Gregory B. (Frontiers in Immunology, 2018)
Pancreatic cancer has a dismal prognosis and effective treatment options are limited. It is projected to be the second most common cause of cancer related mortality in the United States by 2030 and there is urgent unmet need for novel systemic treatment options. Immunotherapy with antibodies targeting PD-1, PD-L1, CTLA-4 has not shown clinical activity in unselected pancreatic cancer, emphasizing the need for combination immunotherapy approaches or other therapeutic strategies. As such, chimeric antigen receptor (CAR) T cell therapy represents an emerging therapeutic option for pancreatic cancer. This modality utilizes genetically engineered T cells that are redirected to a specific cancer-associated antigens to elicit potent cytotoxic activity. This review summarizes the available preclinical data and highlights early phase clinical trials using CAR T cell approaches in pancreatic cancer, a disease state that is gaining attention as a conduit for cell therapy. Future directions in application of CAR T cell therapy are also considered including its ability to be directed against novel epitopes and combined with other therapeutic regimens.